La sociedad esclavista en el Nuevo Reino de Granada: una sociedad humillante - Angela Uribe (Revista de Estudios Sociales, 2007)
A humiliating society: Slaveryin the Kingdom of New GranadaIs humiliation a psychological ora philosophical concept? This article illustrates how trying to privilege either possible way to answer this question leads to difficulties that 1) either limit the possibilities of recognizing humiliation as harmful, or 2) neglect the place for a third person in moral judgments about evil. Given that sometimes the place of this third person is represented in History, the article considers a series of facts to describe and judge the slave society of the New Kingdom of Granada as a humiliating society.